Application of Gesture Data Recognition in a Human-Interactive Leap Motion Sensor Chair - Rasheed, K. (Institute of Electrical and Electronics Engineers Inc., 2021)
Gestural interface has been the subject of research for more than 40 years. The implementation of a novel intuitive and adaptive manipulation scheme is proposed by developing a human-machine communication interface between the Leap Motion controller and the wheel chair. In addition, an algorithm is developed to allow an optimum mapping between the user hand movement, tracked by the Leap Motion controller, and the wheel chair. The system should allow for a more natural human-computer interaction and a smooth manipulation of the wheel chair, by constantly adapting to the user hand tremor or shake. The sensor detects motions and moves the wheelchair accordingly. It will track the movement of the fingers and hands in order to identify the gesture, and then the motors will perform the required action using Arduino. The implementation would specially enhance the quality of living, especially for people with lower limb problems, and would support them in performing some of the essential Activities of Daily Living 'ADLs'. Â© 2021 IEEE.